Growth performance of Shorea leprosula and Hopea odorata in degraded lowland areas, eight years after planting at Ayer Hitam Forest Reserve - Hasanuddin, Husna Izzati (2018)
Rehabilitating riparian buffer is a key to restoring natural stream functions and aquatic habitats. However, studies in this area are still lacking, especially in forest recovery and rehabilitation. Therefore, a study was carried out to evaluate the growth performance of two indigenous species namely Shorea leprosula and Hopea odorata. The line planting technique was employed with a planting distance of 2 m × 2 m. The survival rate percentage and growth performance (diameter and height) were analyzed. The results showed that S. leprosula and H. odorata recorded a high survival rate of 100% (S. leprosula) and 95% (H. odorata). For diameter increment, S. leprosula recorded bigger absolute growth rate of diameter increment at 0.9 mm than H. odorata (0.7mm). In term of height increment, S. leprosula attained higher absolute growth rate of height increment with 6.0 cm than H. odorata (4.0 cm). Based on the Independent-sample t-test conducted, the results for both species were not significantly different. This study indicated that both S. leprosula and H. odorata can be planted in lowland areas which are close to riparian zone for rehabilitation purpose based on their survival rate.